[Cal Poly cheerleaders in the homecoming parade] - Cal Poly San Luis Obispo Audio-Visual Department::::::::: (1965)
Five cheerleaders sit on a red Ford car being driven down Osos Street (at the intersection of Monterey) during the Homecoming Parade.